PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) BIDANG KESEHATAN PT FREEPORT INDONESIA DI ERA PANDEMI COVID-19 - Tarigan, Gita Handayani; Radyati, Maria R. Nindita; Utha, Maria Ariesta (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
The implementation of CSR during the COVID-19 pandemic was constrained due to an uncertain and unprecedented situation, which had an impact on the implementation of CSR program. The purpose of this study is to analyze the CSR program in the health sector during the COVID-19 pandemic carried out by one of the State-Owned Enterprises in Indonesia, namely PT Freeport Indonesia (PTFI), which has been known as one of the companies that has a significant impact to Papua and Indonesia as well. PTFI continues to carry out CSR programs in the health sector as in previous years, as well as providing assistance for the prevention of COVID-19. However, although CSR programs in the health sector are still being carried out, few community empowerment programs are provided, and PTFI has not carried out community empowerment in dealing with health crisis. The implementation of PTFI's CSR program in the health sector during the COVID-19 pandemic faced many challenges. The challenges are mostly technical in nature due to social restrictions and health protocols that must be carried out, as well as matters related to infrastructure to facilitate working remotely.